Arabic Text Clustering Methods And Suggested Solutions For Theme-based Quran Clustering: Analysis Of Literature - Qusay Bsoul; Jaffar Atwan; Rosalina Abdul Salam; Malik Jawarneh (Korea Institute of Science and Technology Information (KISTI), 2024)
Indexed by Scopus